ISO 9000 and performance model: An empirical research of automotive industries in northern region - Saad, Rohaizah; Yusoff, Rushami Zien; Abas, Zakaria (2010)
In the era of intense competition and globalization factors, the survival of the individual firms depends on their abilities to enhance their competitive advantage in the global market. Quality has emerged as a strategic competitive tool for organizational success in the domestic and international market. Many concepts and techniques have been adopted to improve the standard of service and quality of products. Many organizations have reviewed that an effective quality management can enhance their competitive abilities and provide strategic advantages in the marketplace. And the most popular quality management system is ISO 9000. Moreover, ISO 9000 quality management system is designed to provide the support and mechanism to ensure quality product. There are researches conducted on the area of ISO 9000 and its implication towards organizational performance. However, the research findings seem contradicting. These contradict findings may result from different reasons such as the level of management commitment, the type of performance being used and also due to its level of adoption. The intention of the organization ISO 9000 certification rather mixed between internal intention and external forces (customer requirements). Due to the mixed intention, it will influence the level of ISO 9000 adoption. Some organization just implement the basic requirement of ISO 9000 for the sake of conformance purposes but there are organizations that really take advantage of ISO 9000 and implement more than ISO 9000 requirements. Due to that, this paper will propose two models; ISO 9000 conformance model and ISO 9000 as performance model.